Determination of glyphosate and aminomethylphosphonic acid for assessing the quality tap water using SPE and HPLC - Delmonico, Eduardo Luiz; Bertozzi, Janksyn; Souza, Nilson Evelázio de; Oliveira, Cláudio Celestino (Acta Scientiarum. Technology, 2014)
The use of pesticides in agriculture is one of the current problems that may result in contamination of both ground and surface water and groundwater. Considering the environmental importance and the increasing use of herbicides in Maringá region, in the present work methods for extraction and determination of glyphosate (GLYP) and aminomethylphosphonic acid (AMPA) using solid phase extraction (SPE) and high performance liquid chromatography (HPLC) were developed. For SPE, anion exchange resin was used and elution was done with hydrochloric acid 50.0 mmol L-1, achieving recovery rates of 82.5-116.2% and 67.1-104.0% for AMPA and GLYP, respectively. For HPLC determination the analytes were derivatized and injected in the HPLC with a C18 column and using mobile phase consisting of phosphate buffer 0.20 mol L-1 at pH 3.0 and acetonitrile (85:15); the monitoring was done at 240 nm. The analysis was performed in 8 min with the same limit of detection and limit of quantification for AMPA and GLYP of 0.09 and 0.20 mg L-1, respectively. The methods were applied to analysis of public water supply samples and concentrations from 2.1 up to 2.9 Âµg L-1 for AMPA and from 2.3 up to 3.3 Âµg L-1 for glyphosate were found. Â Â